Analyzing the Efficiency Elements of Jurisprudence (Case Study, the Terms of Enjoining the Right and Forbidding the Wrong) - Ã˜Â±Ã˜Â¶Ã˜Â§Ã˜Â¦Ã™ÂŠ Ã˜Â±Ã˜Â§Ã˜Â¯, Ã˜Â¹Ã˜Â¨Ã˜Â¯Ã˜Â§Ã™Â„Ã˜ÂÃ˜Â³Ã™ÂŠÃ™Â† (Ø§ÙØªØ´Ø§Ø±Ø§Øª Ø¯Ø§ÙØ´Ú¯Ø§Ù ÙØ±Ø¯ÙØ³Û Ù Ø´ÙØ¯)
The paper is to examine the objections to the efficiency of some jurisprudential issues especially concerning the matter of enjoining the right and forbidding the wrong through the case study of its terms like: having enough knowledge about the right and the wrong, capability and power, safety, and the chance of impact. It also explores the origins of the harming consequences that have been brought about by such impractical approaches to jurisprudence and religion, the consequences like issuing infeasible or contradictory rulings that have resulted in the suspension of such practices as enjoining the right and forbidding the wrong. Then, it proposes the working methods for improving the efficiency and applicability of such jurisprudential issues.